Summer Internship Project - Shetty, Nikit (ATLAS SkillTech University, 2024)
I completed a one-month internship at Davis Daniels & Co., a certified chartered accounting firm, from June 12 to July 12, 2023. During my internship, I worked in the accounting department, where I gained experience in a variety of tasks, including:  Preparing financial statements  Processing invoices  Maintaining accounts payable and receivable  Filing tax returns (ITR and GST)  Assisting with audit procedures
Project Report on Summer Internship Project (2022-24) Under the Guidance of Prof. Chetana Asbe